Can a Positive School Climate Promote Student Attendance? Evidence From New York City. (April 2021) - Hamlin, Daniel
Nearly 15% of American students are chronically absent from school. To address absenteeism, many states have recently made chronic absence a core component of their school accountability plans. Scholars have theorized that a positive school climate can promote student attendance, but empirical support for this idea is lacking. In this study, the relationship between four student-reported measures of school climate and student attendance are investigated by analyzing two annual school climate surveys (N = 823, 753) from New York City. Results indicate small associations among the four measures of perceived school climate and student attendance. Furthermore, school-level changes in perceived school climate between middle and high school were only marginally associated with student attendance.